Recent Advances on the Applications of Luminescent Pb2+-Containing Metal–Organic Frameworks in White-Light Emission and Sensing - Wang, Li-Xin; Xiang, Jing; Li, Chuan-Hua; Leung, Chi-Fai; Xiang, Jing (Frontiers in Chemistry, 2021)
Luminescent Pb2+-based metal–organic frameworks (MOFs) belong to a new class of multifunctional molecular materials with interesting luminescence properties and potential applications within a single crystalline phase. In this mini review, we present the recent advances that have been achieved in their applications as single-phase white-light emitting materials and chemosensors in the last decade. We focus on the trends in the modification of their structures and luminescence by various bridging ligands, and subsequently their multifunctional applications, which may affect the future development of the field.